Rasgos de personalidad y su relación con el Sexting en jóvenes estudiantes de la Carrera de Administración Pública de la Facultad Jurídica, Social y Administrativa de la Universidad Nacional de Loja. Periodo 2019 - Ríos Córdova, Rodrigo Alberto (2019)
Over the years the practice of sexting has increased among young people and a bad management of that, could result in philological damage; literature suggests the existence of certain personal characteristics which could influence the practice and handling of sexting. The objectives of the present study pretend to establish the relation between personality traits and sexting, as well as the main reasons for it. It was performed a descriptive design-correlational and cross-sectional, in which took part 142 students of the Public Administration career of the National University of Loja, they were also selected using an intentional non-probabilistic sampling. The tools used were: sociodemographic survey, behavior scale on sexting ECS, and personality inventory NEO-FFI-R. The results suggest that the majority of population present a low participation of sexting, among the participants the most common kind of sexting was the passive, the main reason to practice sexting was to want sexual relationships, with respect to personality traits, it was identified a greater presence of amiability, the practice of sexting has a statistically significant relationship with the five traits of personality; being the amiability trait the one with higher correlation. Keywords: personality; personality traits; sexuality; sexting; sexual behavior.